2020
DOI: 10.1155/2020/8464623
|View full text |Cite
|
Sign up to set email alerts
|

High-Score US-Suspicious Subcentimeter Thyroid Nodules: What Factors Affect Adequate Sampling of US-Guided Fine-Needle Aspiration Biopsy?

Abstract: Background. Fine-needle aspiration biopsy (FNAB) is diagnostic standard for thyroid nodules. However, the influence of adequate sample rate of US-guided FNAB for subcentimeter thyroid nodules is not known well. Objectives. To assess the factors affecting adequate sample rate of US-guided FNAB for subcentimeter thyroid nodules. Methods. Three hundred and forty-nine consecutive US-guided FNAB procedures were performed in 344 patients with subcentimeter thyroid nodules. The adequate sample rate was analyzed for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 26 publications
(49 reference statements)
1
5
0
Order By: Relevance
“…Similarly, studies by Leenhardt et al., Leung et al., Li et al., and Chen et al. observed a comparable relationship in FNA for thyroid nodules ( 10 , 18 , 28 , 29 ). Conversely, other studies found no significant correlation between nodule MD and sample adequacy in FNA ( 12 , 15 , 30 , 31 ).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Similarly, studies by Leenhardt et al., Leung et al., Li et al., and Chen et al. observed a comparable relationship in FNA for thyroid nodules ( 10 , 18 , 28 , 29 ). Conversely, other studies found no significant correlation between nodule MD and sample adequacy in FNA ( 12 , 15 , 30 , 31 ).…”
Section: Discussionsupporting
confidence: 58%
“…Besides MD, numerous studies have identified various factors potentially influencing FNA outcomes in thyroid nodules ( 10 , 12 16 , 18 , 28 30 , 32 , 33 ), including age ( 14 ), needle path ( 18 ), needle size ( 11 ), calcification ( 10 , 12 , 18 ), echogenicity ( 14 , 16 ), composition ( 13 ), shape ( 12 ), the depth of nodule ( 29 , 30 ), and Hashimoto thyroiditis ( 12 ) et al. However, these studies primarily focused on factors influencing non-diagnostic outcomes (Bethesda I or III), with few examining the potential factors impacting malignant outcomes in FNA of thyroid nodules.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid nodules with high inadequate risk have a significantly higher inadequate rate after US-FNA in our study, comparing with the overall 3748 nodules in our center (16.7% vs. 6.6%, P < 0.001) or some other centers [ 17 ]. They have some common US features, such as high cystic composition, mixed cystic and solid nodules with hemorrhage, or suspicious degenerating nodules [ 4 , 6 ]. For instance, the inadequate rates of US-FNA in cystic, predominantly cystic, predominantly solid and solid subgroups are 28.1%, 17.1%, 10.0% and 9.2% ( P = 0.019), which indicating that the amount of cystic component is an important factor affecting specimen adequacy.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that composition of thyroid nodules has a definite effect on acquiring specimen during US-FNA. Thyroid nodules with high cystic component [ 4 , 5 ], hemorrhage or with macrocalcification [ 6 ] have higher risk of specimen inadequacy [ 7 ]. Meanwhile, solid nodule undergo reduction in size, which is known as degenerating nodules with malignant US features, often result in lower specimen acquisition [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, in clinical practice, many patients prefer not to forego further evaluation and insist on proceeding with FNAB. Sample adequacy represents an important issue with FNAB sampling of subcentimeter nodules and has been reported to be as low as 72.2% for 3-to 6-mm nodules, 84.9% for 7-to 10-mm nodules, and 63% in the presence of macrocalcifications (60). TSH suppression therapy to shrink TN in euthyroid individuals was in vogue for many years, and a metaanalysis published in 2005 found an 88% likelihood of achieving a reduction in nodule volume of greater than compared with placebo or no treatment (61).…”
Section: Managementmentioning
confidence: 99%